Kinerja Guru di SD Negeri Gugus 1, Kecamatan Lubuk Besar, Kabupaten Bangka Tengah: Pengaruh Kompetensi Guru Dan Sertifikasi Guru - Agus Taruno AD; Yasir Arafat; Muhammad Juliansyah (Journal on Education, 2023)
This study aims to ascertain the impact of teacher certification and competence on teacher achievement in Lubuk Besar District, SD Negeri Gugus 1, Central Bangka Regency. In SD Negeri Gugus 1, 61 teachers were included in the sample. Purposive sampling was the sampling strategy used, and the respondents were several teachers from Gugus 1 Public Elementary School in Lubuk Besar District, Central Bangka Regency. A 5-point Likert scale was used to measure the 90 statement items on the distributed questionnaire to collect data. Multiple linear regression analysis is the method used for analysis. The results of the study show that teacher competence and certification have an impact on teacher performance. Second, teacher competence has an impact on performance. Third, teacher certification has an impact on performance.